Awareness and attitudes toward corneal donation: challenges and opportunities - Williams AM (Dove Medical Press, 2018)
Andrew M Williams,1 Kelly W Muir2,3 1Department of Ophthalmology, University of Pittsburgh Medical Center, Pittsburgh, PA, USA; 2Department of Ophthalmology, Duke University Medical Center, Durham, NC, USA; 3Durham VA Medical Center, Health Services Research and Development, Durham, NC, USA Abstract: There is a severe shortage of donor corneas available worldwide for transplantation, with the number of patients in need of transplant greatly exceeding the number of cornea tissues available. Understanding awareness and attitudes about corneal donation worldwide is a critical step toward addressing this shortage. In this review, awareness of corneal donation and reported willingness to donate are summarized from 55 published studies across 13 countries. In general, many more respondents indicated positive attitudes toward eye donation and willingness to donate their eyes than the number of respondents who have pledged their eyes for donation, suggesting an unrealized potential of additional donors. Specifically, of 38,851 respondents across all included studies, 52% endorsed a willingness to donate their eyes after death, yet only 5% reported being a pledged donor. The most commonly cited reason for not being a registered eye donor was lack of awareness about eye donation. The disconnection between the large number of people who expressed willingness to donate and the scarcity of individuals who have pledged their eyes for donation could be addressed through educational media campaigns, collaborations with medical personnel, partnerships with grief counselors and religious leaders, use of social media, and educational sessions with medical students and staff. Keywords: eye donation, corneal transplantation, attitudes, eye bank, organ donation